2005
DOI: 10.1103/physrevb.72.155113
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties in correlated systems: An analytical model

Abstract: Several studies have so far investigated transport properties of strongly correlated systems. Interesting features of these materials are the lack of resistivity saturation well beyond the Mott-IoffeRegel limit and the scaling of the resistivity with the hole density in underdoped cuprates. Due to the strongly correlated nature of these materials, mainly numerical techniques have been employed. A key role in this regards is thought to be played by the continuous transfer of spectral weight from coherent to inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Matthiessen's rule is expected to be broken when in the saturation region when the resistivity approaches the Ioffe-Regel limit, because there is essentially a minimum mean free path -the nearest-neighbor distance [39]. Previous studies [40,41] have shown that, for strongly-correlated systems, resistivity can far exceed the Ioffe-Regel limit, corresponding to a very short mean free path. Therefore, when e-ph and e-e scattering contributions are comparable to each other, it may be suitable to consider saturation effects only on the e-ph part and apply Matthiessen's rule after having considered saturation.…”
mentioning
confidence: 99%
“…Matthiessen's rule is expected to be broken when in the saturation region when the resistivity approaches the Ioffe-Regel limit, because there is essentially a minimum mean free path -the nearest-neighbor distance [39]. Previous studies [40,41] have shown that, for strongly-correlated systems, resistivity can far exceed the Ioffe-Regel limit, corresponding to a very short mean free path. Therefore, when e-ph and e-e scattering contributions are comparable to each other, it may be suitable to consider saturation effects only on the e-ph part and apply Matthiessen's rule after having considered saturation.…”
mentioning
confidence: 99%
“…S7 and discussion in Supplemental Material [18], which includes Refs. [48][49][50][51][52][53][54]). Neither the present calculations, nor those in Ref.…”
mentioning
confidence: 99%
“…Specific long-range correlation in complex systems are 936 the object of active research due to its implications in the 937 technology of materials and in several fields of scientific 938 knowledge with the use of quantified histograms [78], de-939 crease of chaos in heart failure [85], scaling properties 940 of ECG's signals fluctuations [87] , transport properties in 941 correlated systems [88] etc.…”
mentioning
confidence: 99%